IMPROVING WRITING ABILITY OF X GRADE STUDENTS AT SMK N 1 GALANG THROUGH DISCOVERY LEARNING - Ismail Yunus H (Universitas Madako Tolitoli, 2019)
The objective of the research is to find out whether the Discovery Learning can improve students’ writing ability in recount text or not. This research use X ATPH2 class which consists of 23 students as the sample. The procedure of this research consists of pretest, treament and posttest. The researcher gives pretest and posttest to know the improvement of students’ writing ability after they are taught by using discovery learning method. The result of this research shows that there is significant improvement after the students are taught by using discovery learning method. It is proven by significant improvement on student’ score in posttest. The mean score of pretest is 57.74 while the the mean score of posttest is 74.00. The data both pretest and posttest were analyzed by using T-test formula. The result shows that T-test value 8.212 greater that T-table value 2.074. It means that discovery learning method can improve students’ writing ability. Keywords: Improving, Writing Ability, Recount Text, Discovery Learning